2021
DOI: 10.47059/revistageintec.v11i4.2162
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Russian Transport and Logistics Potential in the Export of Grain Products

Abstract: The article reflects the current state of logistics transport capabilities aimed at expanding the trade potential of the Russian agro-industrial complex on the example of the grain industry. The authors note that one of the components of successful foreign economic relations is the degree of development of distribution processes both within a single state and in the global economy. The transport capabilities of an individual state affect the intensity of trade relations no less than resource and production one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…At the same time, the authors consider the increase of spatial market efficiency of grain markets in Russia as the driver of increasing the country's export potential. Together, the conducted study of the state of Russian transport capabilities has revealed the lack of development of the latter, especially railway transport and grain transshipment capabilities in seaports, which prevents an increase in the volume of grain exports to strategic foreign partners [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, the authors consider the increase of spatial market efficiency of grain markets in Russia as the driver of increasing the country's export potential. Together, the conducted study of the state of Russian transport capabilities has revealed the lack of development of the latter, especially railway transport and grain transshipment capabilities in seaports, which prevents an increase in the volume of grain exports to strategic foreign partners [5].…”
Section: Literature Reviewmentioning
confidence: 99%